Penerapan Teknologi Droplet Nanofluida Pada Alat Penyemprot Disinfektan dalam Upaya Pencegahan Penyebaran Covid-19 Pada Fasilitas Umum di Kec. Pakisjaya Kab. Karawang - Reza Setiawan; Aripin Aripin; Agustian Suseno; Vera Pangni Fahriani (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
PkM Tanjung Bungin Village, Karawang Regency is inhabited by 891 families or around 2,612 residents. Crowded places such as entertainment venues, sales of fishermen's catches and traditional markets are always busy with people from villages, sub-districts and even Bekasi Regency. Frequent interactions between the people of Tanjung Bungin Village and people outside the village area because of the necessities of life that need to be met have resulted in a large potential for the spread of Covid-19. There needs to be a program that can provide the right solution to prevent the spread of Covid-19. Application of Nanofluid Droplet Technology in Disinfectant Sprayers in Efforts to Prevent the Spread of Covid-19 in Public Facilities in Kec. Pakisjaya District. Karawang independently among the community is one of the appropriate and effective solutions. The disinfectant sprayer made is based on the theory underlying research proposed on microsprayer technology on disinfectant sprayers made and used in PkM efforts to prevent the spread of Covid-19 in public facilities in Pakisjaya District, Kab. Karawang. The method that had been used was by mentoring, training, making and implementing Disinfectant Spray Equipment. The output of this community service activity was the creation and implementation of a nanofluid droplet technology disinfectant sprayer at public facilities in Tanjungbungin Village, Pakisjaya District, Karawang Regency.